ErbB4 as a Potential Molecular Target in the Treatment of Esophageal Squamous Cell Cancers - Ke Zhao; Bao-Jun Chen; Zhi-Guo Chen (The Scientific World Journal)
ErbB4 is an important member of ErbB subfamily of tyrosine kinases receptor with overexpression in several tumors; however its biological role in esophageal cancer is poorly understood till date. The main objective of this study was to examine whether miRNA-140-5p could target and control ErbB4 expression at transcriptional level. The ErbB4 expressions in different cell lines were evaluated by western blotting and luciferase assay. Moreover, cell proliferation, apoptosis, and cell invasion studies were investigated using MTT, flow cytometry, and transwell assays. miRNA-140-5p remarkably downregulated the ErbB4 expression in EC9706 and TE-1A cell lines. Furthermore, miRNA-140-5p transfected cell significantly controlled the cell proliferation and enhanced the apoptosis of multiple cells. Additionally, miRNA-140-5p had marked effect on the DNA synthesis and caspase 3/7 activity in comparison to control cells. Specifically, miRNA-140-5p inhibited/repressed the cancer cell invasion and migration in a sign to have important biological role in esophageal carcinomas. Taken together, miRNA-140-5p could act as a potential molecular target in ErbB4 overexpressing ESCC cell lines paving the way for effective esophageal cancer treatment.